Development of a gas environmental heating specimen holder system using differential pumping. (15th June 2021) - Hashimoto, Ayako; Han, Yutain; Akimoto, Hajime; Hozumi, Ryo; Takeguchi, Masaki
Abstract: We developed a gas environmental heating specimen holder system by applying differential pumping effect to a specimen holder for the in situ transmission electron microscopy observation and electron energy loss spectroscopy (EELS) analysis of catalytic materials. In the in situ experiments, using two small orifices and O-rings, the maximum formed gas pressure was ∼20 Pa. Also, using a heater membrane, the maximum obtained heating temperature was ∼1000°C. We could actually observe/analyze the Pt and Ni nanoparticles with an atomic scale using a double-aberration-corrected microscope and an EELS instrument in the reaction gases at high temperatures.